(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Flores ABA, Mondejar EP, Caballero EB, Maceda JN, Olowa LF, Nuñeza OM. 2025. Diversity and composition of anurans on Mount Gutom Protected Landscape, Zamboanga del Norte, Philippines. Biodiversitas 26: 3769-3780. Mount (Mt.) Gutom Protected Landscape is among the last remaining natural forests and serves as one of the most critical watersheds in Zamboanga del Norte, Philippines. Despite its ecological importance, no comprehensive studies on anuran species have been conducted in the area, leaving a significant gap in our understanding of the area’s amphibian biodiversity and its conservation needs. This study investigates the species composition, abundance, and conservation status of anurans in the Mt. Gutom Protected Landscape. An opportunistic sampling method was employed at four sites: Sikitan, Malikas, Lower Gutom, and Upper Gutom. A total of 269 individuals representing 19 species from six families were recorded, with the highest species richness observed in Sikitan and Malikas. Notably, 12 species (63.16%) are endemic to the Mindanao Faunal Region, while three (15.79%) species are Philippine endemics, and the remaining are native (21.05%) to the country but more widely distributed. The Near Threatened species Limnonectes magnus was recorded as the most abundant and dominant species. According to the Bray-Curtis similarity analysis, two distinct site clusters (Sikitan-Malikas and Lower-Upper Gutom) indicate habitat differences that influence species distribution. SIMPER analysis confirmed that L. magnus contributed significantly to observed dissimilarities. Diversity indices revealed substantial variation: Malikas had the highest Shannon diversity index (H?: 2.328) and the lowest dominance index (D: 0.1208), reflecting a balanced and less disturbed habitat. Sikitan followed closely (H?: 2.205, D: 0.1431). In contrast, Lower Gutom (H?: 1.819, D: 0.2535) and Upper Gutom (H?: 1.489, D: 0.3399) exhibited higher dominance and lower diversity, suggesting anthropogenic pressures. These results highlight the ecological importance and site-specific vulnerabilities of Mt. Gutom’s anuran communities, emphasizing the need for urgent conservation interventions, including habitat protection, continued monitoring, and community-based stewardship programs to safeguard these endemic and threatened amphibians.